THE RESULTS OF SOCIOLOGICAL RESEARCH ON THE ISSUES OF NATIONAL SECURITY IN MONGOLIA - Nergui Bayartogtokh; Oyuntsetseg Densmaa; Uranchimeg Tumurbat; Batbayar Dashzeveg (International Journal of Innovative Technologies in Social Science, 2025)
Determine the national security guarantee of Mongolia, the dangers and threats it may cause, based on the opinions of the people, determine the level of patriotism of the citizens, analyze the current and future threats and risks, and study the values and opinions of the citizens regarding policies and activities, published the results of the following expert sociological research in order to identify the problems in the field of civil-military relations and security.